Vivere La Speranza Nella Difficoltá E Nella Prova: Aspetti Psicologici E Istanze Educative - Del Core, Pina (Rivista di scienze dell'educazione, 2021)
Faced with crisis and uncertainty about the future, the suffering and anguish that surprise us when we experience loss, separation, death, and tragic events such as the pandemic, not everyone has the capacity to resist and bear the burden of trials. Hope, optimism, resilience, the capacity to make plans, and the search for meaning are important factors that help us overcome the trials and adversities of life. An in-depth understanding of these psychological necessities compared with Frankl's thought on the meaning of suffering offers interesting starting points for reflection by those who work in the educational field. They can indicate paths for formation in terms of content and attitudes that can offer a perspective of hope to guide one towards searching for meaning and accomplishing the unique and unrepeatable purpose of one's own existence.